2008
DOI: 10.1111/j.1601-5223.1992.tb00173.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of genetic and environmental factors on the a-b, b-c and c-d interdigital ridge counts

Abstract: A study of 100 MZ (55 female and 45 male) and 97 DZ (50 male and 47 female) same-sexed twin pairs was carried out to analyse the genetic component of the variance of the a-b, b-c and c-d interdigital ridge counts by means of the Christian method. Especially for the a-b interdigital ridge count, we found it important to analyse both sexes separately. Our results suggest that the a-b count in males seems to be more influenced by environmental factors than the other counts. For females, the three interdigital cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
0
6
1
Order By: Relevance
“…For this reason, digital dermaglyphics undergo intrauterine environmental influences for a shorter time than palmar and plantar dermatoglyphics. It is also documented that women are less susceptible to changes in dermatoglyphic characteristics in comparison to men 4,9 . The present study has revealed only digital dermaglyphics differences rather than palmar dermatoglyphics in females.…”
Section: Manova For 14 Variables (Factorial Model For Sex and Groups)contrasting
confidence: 41%
“…For this reason, digital dermaglyphics undergo intrauterine environmental influences for a shorter time than palmar and plantar dermatoglyphics. It is also documented that women are less susceptible to changes in dermatoglyphic characteristics in comparison to men 4,9 . The present study has revealed only digital dermaglyphics differences rather than palmar dermatoglyphics in females.…”
Section: Manova For 14 Variables (Factorial Model For Sex and Groups)contrasting
confidence: 41%
“…The prenatal sex differences in environmental sensitivity may be significant with respect to dermatoglyphic sexual dimorphism (Micle and Kobyliansky, 1991;Karmakar et al, 2003). Arrieta et al (1992) studied palmar a-b, b-c and c-d ridge counts in twins, with a-b ridge count corresponding to the II interdigital area, b-c to the III interdigital area, and c-d to the IV interdigital area, and concluded that the interdigital counts are more or less genetically independent. They found differences in the genetic and/or environmental influences on interdigital ridge counts, both between the sexes and between the right and left hand.…”
Section: Discussionmentioning
confidence: 97%
“…Heredity of quantitative dermatoglyphic traits conforms to polygenic system, with individual genes contributing a small additive effect, but the prenatal environment may also exert an important influence [2]. Finger ridge count is one of the most heritable anthropometric features, and has been used as a model trait for the study of human quantitative genetics [7,29].…”
Section: Introductionmentioning
confidence: 99%